2019
DOI: 10.1101/610071
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Projected climate change will reduce habitat suitability for bumble bees in the Pacific Northwest

Abstract: 21Global climate change is the greatest environmental challenge of the modern era. The impacts of 22 climate change are increasingly well understood, and have already begun to materialize across 23 diverse ecosystems and organisms. Bumble bees (Bombus) are suspected to be highly sensitive to 24 climate change as they are predominately adapted to temperate and alpine environments. In this 25 study, we determine which bumble bee species are most vulnerable to climate change in the 26 Pacific Northwest. The Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Our results highlight important research avenues into mechanisms by which bumble bees and other insects may adapt to climatic stresses, and thus have ecological and conservation implications. As low elevation organisms move upslope from thermal niche shifts, ranges for montane Bombus will probably erode (Koch et al, ), but other aspects of climate variation (e.g., seasonality, precipitation) could remain mismatched and lead to complex climate change responses (Dillon & Lozier, ; Kerr et al, ). Continued observation of this system will give additional clues about species characteristics that ease or hinder adaptation to changing bioclimatic landscapes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results highlight important research avenues into mechanisms by which bumble bees and other insects may adapt to climatic stresses, and thus have ecological and conservation implications. As low elevation organisms move upslope from thermal niche shifts, ranges for montane Bombus will probably erode (Koch et al, ), but other aspects of climate variation (e.g., seasonality, precipitation) could remain mismatched and lead to complex climate change responses (Dillon & Lozier, ; Kerr et al, ). Continued observation of this system will give additional clues about species characteristics that ease or hinder adaptation to changing bioclimatic landscapes.…”
Section: Discussionmentioning
confidence: 99%
“…Precipitation is also likely to have direct (e.g., desiccation pressure) or indirect (e.g., availability of floral resources) effects on bee fitness (Nicolson, 2009). Previous studies have also found that precipitation variables can be the most informative for predicting bumble bee ranges (Jackson et al, 2018;Koch, Looney, Hopkins, Lichtenberg, & Walter, 2019). As with temperature, we considered variables capturing means, extremes, and variability: Annual precipitation, precipitation of the wettest/driest months, and precipitation seasonality.…”
Section: Outlier Detection and Cross-validation Across Eaa Methodsmentioning
confidence: 99%
“…The results and approach of our study may be helpful for the prevention and early detection of invasive insects, namely bees, in determining suitable niches outside of their native range. The development of SDMs is a useful approach in determining how bees and other insects will expand outside of their native niche [ 1 , 45 , 59 ]. However, it is also clear that there are limitations to SDMs in predicting the invasive spread of bees, as evidenced by data collected during ground surveys of invasive A. manicatum in northeastern North America [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we performed a linear regression analysis between genetic distance (standardized by F ST /(1− F ST )) and geographical distance (log 10 transformed). Precipitation, sunshine duration (i.e., the time of effective solar radiation during the day without cloud cover), and average temperature were considered as the most effective predictors of bee ranges (Jackson et al, 2018 ; Koch et al, 2019 ). We obtained these surface meteorological data from 2010 to 2016.…”
Section: Methodsmentioning
confidence: 99%